Comparison of Dopamine and Norepinephrine Use for the Treatment of Hypotension in Out-Of-Hospital Cardiac Arrest Patients with Return of Spontaneous Circulation - Chao-Jui Li; Kuan-Han Wu; Chien-Chih Chen; Yat-Yin Law; Po-Chun Chuang; Yi-Chuan Chen (Emergency Medicine International)
In patients experiencing out-of-hospital cardiac arrest (OHCA), hypotension is common after return of spontaneous circulation (ROSC). Both dopamine and norepinephrine are recommended as inotropic therapeutic agents. This study aimed to determine the impact of the use of these two medications on hypotension. This is a multicenter retrospective cohort study. OHCA patients with ROSC were divided into three groups according to the post resuscitation inotropic agent used for treatment in the emergency department, namely, dopamine, norepinephrine, and dopamine and norepinephrine combined therapy. Thirty-day survival and favorable neurologic performance were analyzed among the three study groups. The 30-day survival and favorable neurologic performance rates in the three study groups were 12.5%, 13.0%, and 6.8% as well as 4.9%, 4.3%, and 1.2%, respectively. On controlling the potential confounding factors by logistic regression, there was no difference between dopamine and norepinephrine treatment in survival and neurologic performance (adjusted odds ratio (aOR): 1.0, 95% confidence interval (CI) 0.48–2.06; aOR: 0.8, 95% CI: 0.28–2.53). The dopamine and norepinephrine combined treatment group had worse outcome (aOR: 0.6, 95% CI: 0.35–1.18; aOR: 0.2, 95% CI: 0.05–0.89). In conclusion, there was no significant difference in post-ROSC hypotension treatment between dopamine and norepinephrine in 30-day survival and favorable neurologic performance rates.